Evolutionary Divergence of Marinobacter Strains in Cryopeg Brines as Revealed by Pangenomics - Cooper, Zachary S.; Rapp, Josephine Z.; Shoemaker, Anna M. D.; Anderson, Rika E.; Zhong, Zhi-Ping; Deming, Jody W. (Frontiers in Microbiology, 2022)
Marinobacter spp. are cosmopolitan in saline environments, displaying a diverse set of metabolisms that allow them to competitively occupy these environments, some of which can be extreme in both salinity and temperature. Here, we introduce a distinct cluster of Marinobacter genomes, composed of novel isolates and in silico assembled genomes obtained from subzero, hypersaline cryopeg brines, relic seawater-derived liquid habitats within permafrost sampled near Utqiaġvik, Alaska. Using these new genomes and 45 representative publicly available genomes of Marinobacter spp. from other settings, we assembled a pangenome to examine how the new extremophile members fit evolutionarily and ecologically, based on genetic potential and environmental source. This first genus-wide genomic analysis revealed that Marinobacter spp. in general encode metabolic pathways that are thermodynamically favored at low temperature, cover a broad range of organic compounds, and optimize protein usage, e.g., the Entner-Doudoroff pathway, the glyoxylate shunt, and amino acid metabolism. The new isolates contributed to a distinct clade of subzero brine-dwelling Marinobacter spp. that diverged genotypically and phylogenetically from all other Marinobacter members. The subzero brine clade displays genomic characteristics that may explain competitive adaptations to the extreme environments they inhabit, including more abundant membrane transport systems (e.g., for organic substrates, compatible solutes and ions) and stress-induced transcriptional regulatory mechanisms (e.g., for cold and salt stress) than in the other Marinobacter clades. We also identified more abundant signatures of potential horizontal transfer of genes involved in transcription, the mobilome, and a variety of metabolite exchange systems, which led to considering the importance of this evolutionary mechanism in an extreme environment where adaptation via vertical evolution is physiologically rate-limited. Assessing these new extremophile genomes in a pangenomic context has provided a unique view into the ecological and evolutionary history of the genus Marinobacter, particularly with regards to its remarkable diversity and its opportunism in extremely cold and saline environments.